Thinking through the body of the law. Pheng Cheah, David Fraser and Judith Grbich (eds) - Julia Quilter (Law Text Culture, 1997)
Thinking Through the Body of the Law (1996) is a pathbreaking book which should presage further works of its kind. While the essays are more diverse than coherent, there is a general attempt to supplement Critical Legal Studies, Feminist Jurisprudence and Critical Race Theories' re-conceptualisation of the Law as something other than an isolated practice of objective and impartial rules. The authors question our understanding of ethics, embodiment, the social and law/justice. In doing so they present us with an inspiring range of trajectories which call for further research. In this respect, the title of the book sets an overly ambitious agenda. The title performatively asserts that the 'thinking' that is done in this book accomplishes a 'thinking through the body of the law.' This presumes a movement involving destination and arrival; parameters which seem both an impossibility and an undesirability given the subject. To re-conceptualise ethics, embodiment and law-justice, as Patton attests in the book, requires us to find 'new fonns' (p.59) that will not be known in advance of the process nor be final in their 'specific detenninations.' (p.59)